Retrospective analysis of ranula patients managed with surgical treatment - Altın, Fazilet; Alimoğlu, Yalçın (ENT Updates, 2020)
Objective: We aimed to examine patient characteristics, recurrence rate and efficacy of treatment methods in patients who underwent surgery with the diagnosis of ranula in our department retrospectively. The subject is discussed in the light of current literature. Methods: Twenty-seven patients with ranula managed surgically between 2008 and 2018 were included in this study. The indications, age and sex distribution, surgical pathology reports, surgical methods, complications encountered and recurrence rates were examined retrospectively. Results: The mean age was 27.48±18.66 years. There were 8 (29.6%) male and 19 (70.4%) female cases. The mean size of the ranula was 3.07±0.35 cm. When the symptoms were evaluated, 23 (85.2%) of the patients had a swelling in the floor of the mouth, 3 (11.1%) had a neck swelling and 1 (3.7%) had swelling on the lower surface of the tongue. The treatment method was marsupialization in 11 (40.7%) patients and ranula cyst excision in 16 (59.3%) patients. Four (14.8%) of these patients had a recurrence. The first surgical procedure was marsupialization in 3 (75%) and cyst excision in 1 (25%) of the cases with recurrence. Of the patients with recurrence, 3 subsequently underwent cyst excision and 1 of the patients underwent marsupialization. No complication or additional recurrence was observed in the follow-up of these patients. Conclusions: Concerning our ten years of experience with the management of ranula, we can conclude that ranula can be treated by both marsupialization and cyst excision with a low risk of recurrence.